EGGS QUALITY IN FUNCTION OF THE SPACE HETEROGENITY OF THE INTERNAL ENVIRONMENT FROM THE PRODUCTION SHED - PEREIRA, DANILO F.; BARATO, FERNANDO F.; TOGASHI, CRISTINA K.; GABRIEL FILHO, LUIS R. A.; SAMPAIO, FÁBIO F. (Revista Brasileira de Engenharia de Biossistemas, 2008)
Egg production losses can be measured by the reduction of the number eggs production inquality. The rise of laying hens mortality in different areas of the same aviary is possible andrepresent significant losses to the producer . Methods of geostatistics and mathematics can beutilized to analyze and interpret the spatial variations of variables within the aviary ;such asenvironment and egg quality. The data of the environment were recorded in a single day ofSeptember, in four hours (9h, 12h, 15h and 18h), and spatial variability of each variable for eachtime the record was analyzed by the method of kriging geostatistics. From this analysis weredefined distinct regions to the environment and egg samples were collected within two days followingthe collection of environmental data. There are significant differences between the samples ofeggs for the measures the weight of the egg, the shell weight and specific gravity, but not alldifferences were noted variables associated with the environmental measures, indicating that otherenvironmental variables may be affecting the production.